2021
DOI: 10.1007/s42729-021-00411-5
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement in Plant Growth and Zinc Biofortification of Chickpea (Cicer arietinum L.) by Bacillus altitudinis

Abstract: Zinc-solubilizing bacteria (ZSB) are potential and ideal substitutes for Zn supplement. Currently, limited reports are available on the bacteria displaying capability to transform insoluble forms of zinc (Zn) to an available form. Therefore, attempts were made to identify and characterize Zn-solubilizing strains from chickpea rhizosphere for growth promotion and Zn biofortification. Sixtyone bacteria isolated from rhizosphere of chickpea from different parts of Indo-Gangetic plains (IGP) of India were screened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 85 publications
(113 reference statements)
1
26
0
Order By: Relevance
“…In the past few decades, PGPR that belong to the species of Bacillus isolated from the rhizosphere and marine sources have been used for plant growth promotion. The Bacillus species are preferred for their use in agriculture due to their ability to produce bioactive metabolites and endospores to withstand biotic and abiotic stress conditions, which thereby promote plant growth and nutrient uptake [16][17][18][19]. In the present study, Bacillus spp., isolated from marine water and the rhizosphere, were evaluated for improvement in growth, yield, and iron content in sorghum under in vitro and in vivo conditions.…”
Section: Introductionmentioning
confidence: 88%
“…In the past few decades, PGPR that belong to the species of Bacillus isolated from the rhizosphere and marine sources have been used for plant growth promotion. The Bacillus species are preferred for their use in agriculture due to their ability to produce bioactive metabolites and endospores to withstand biotic and abiotic stress conditions, which thereby promote plant growth and nutrient uptake [16][17][18][19]. In the present study, Bacillus spp., isolated from marine water and the rhizosphere, were evaluated for improvement in growth, yield, and iron content in sorghum under in vitro and in vivo conditions.…”
Section: Introductionmentioning
confidence: 88%
“…Grains, vegetables, and fruits fortified with Zn can effectively overcome Zn malnutrition. Therefore, the availability of the required Zn is an imperative factor in enhancing the overall crop yield (160,164). The poor supply of Zn ultimately leads to the reduced productivity of the plants with an insufficient accumulation of Zn in their edible portions (165).…”
Section: Scenario Of Microbial Inoculants In Zn Exemplification In Plantsmentioning
confidence: 99%
“…Previous studies have shown that the sequencing of bacterial inoculants (especially Bacillus sp.) had the potential to better solubilize Zn insoluble complexes, including phosphate, oxides, and carbonates, and make them available for plant uptake and therefore improve the growth attributes of leguminous crops [35,52]. Several previous studies have indicated that different strains of Bacillus, Pseudomonas, and Rhizobium sp.…”
Section: Discussionmentioning
confidence: 99%